1992
DOI: 10.1016/0735-1097(92)90342-k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flecainide on the rate dependence of atrial refractoriness, atrial repolarization and atrioventricular node conduction in anesthetized dogs

Abstract: 1) Flecainide suppresses atrial action potential duration accommodation to heart rate changes in vivo, leading to rate-dependent atrial effective refractory period prolongation, which may be important in suppressing atrial fibrillation. 2) The drug has frequency- and direction-dependent effects on AV node conduction, which may lead to selective antiarrhythmic actions during AV node reentry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…20,34 A flecainide-induced reduction in aERP accommodation to atrial activation rates, which may be important in suppressing AF, has been demonstrated by others. 18,[34][35][36] However, this mechanism of rate-dependency and increased drug action at rapid atrial activation rates could not be proven by the present study. Still, despite the lack of aERP prolongation at the atrial rates measured in the present study, we cannot rule out possible increases in 136.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…20,34 A flecainide-induced reduction in aERP accommodation to atrial activation rates, which may be important in suppressing AF, has been demonstrated by others. 18,[34][35][36] However, this mechanism of rate-dependency and increased drug action at rapid atrial activation rates could not be proven by the present study. Still, despite the lack of aERP prolongation at the atrial rates measured in the present study, we cannot rule out possible increases in 136.…”
Section: Discussioncontrasting
confidence: 69%
“…In humans, some reported a slight but not significant flecainide‐induced increase in aERP, whereas others reported significant and use‐dependent increases 20, 34. A flecainide‐induced reduction in aERP accommodation to atrial activation rates, which may be important in suppressing AF, has been demonstrated by others 18, 34, 35, 36. However, this mechanism of rate‐dependency and increased drug action at rapid atrial activation rates could not be proven by the present study.…”
Section: Discussionmentioning
confidence: 90%
“…11 Katritsis et al also reported that flecainide prolonged atrial ERP during sinus rhythm, but not during atrial pacing at any heart rate. 12 O'Hara et al 13 and Hodess et al 14 reported that atrial ERP prolongation was more pronounced when flecainide was administered in dogs with pharmacological autonomic nerve block. Although we did not compare the effects in the presence or absence of autonomic nerve block, the sympathetic nerve activity in the present study was expected to be low because of the deep sedation induced by administration of midazolam and fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…41 Flecainide also suppresses atrial APD accommodation to heart rate changes in anaesthetized dogs, leading to rate-dependent prolongation of atrial refractoriness, which may be important in suppressing AF. 42 In an experimental canine models of AF, flecainide terminates AF by causing a tachycardia-dependent increase in atrial effective refractory period and wavelength, reducing the number of re-entrant circuits, so that the arrhythmia can no longer sustain itself. 43,44 However, in goats instrumented with multiple atrial electrodes, cardioversion of sustained AF induced by flecainide could not be attributed to a prolongation of atrial wavelength but to a progressive widening in the temporal excitable gap during AF.…”
Section: Focus On Flecainidementioning
confidence: 99%